The differential diagnosis of longitudinally extensive transverse myelitis. - Kitley, J; Leite, M; George, J; Palace, J (2012)
Longitudinally extensive transverse myelitis refers to florid and widespread inflammation of the spinal cord causing T2 hyperintensity on spinal magnetic resonance imaging that is seen to extend over three or more vertebral segments. Whilst rare, longitudinally extensive transverse myelitis is clinically important as it can lead to catastrophic morbidity, and a group of these patients are at risk of further attacks. Early identification and establishment of the underlying aetiology is vital in order to initiate appropriate therapy and optimize outcomes. Whilst longitudinally extensive transverse myelitis is classically associated with neuromyelitis optica, there are many other causes. These include other inflammatory aetiologies, infection, malignancy and metabolic disturbance. Some of these are readily treatable. Laboratory and radiological investigations can help to differentiate these causes. Treatment of longitudinally extensive transverse myelitis hinges on distinguishing inflammatory and non-inflammatory aetiologies and identifying patients who are at high risk of a recurrent course.